Implementation Of Immigration Policy On Foreign Workers During The Covid-19 Pandemic - Dimas Sutan Firmansyah Agam; I Dewa Gede Mahesa Pradnyadinata; Nurshifa Namira Jafarisy (IHSA Institute, 2021)
As there is foreign worker (TKA), it is also a foreign investment with the aim for the welfare of the people in Indonesia. This is stated in Law No. 13 of 2003 related to Employment which provides labor protection where the basic rights are guaranteed by the company and there is no discrimination between workers. With the impact of the covid pandemic in Indonesia, of course, Immigration becomes an important role in dealing with the pandemic by limiting the movement related to people traffic in the territory of Indonesia both for foreigners with tourist destinations and up to foreign workers, surely is a major change and shift to the order of life both in terms of health, social and economic. This research uses normative type research, which is included in deductive research where it starts from an analysis of provisions related to laws and regulations that regulate the issue of immigration implementation at the time of pandemic. The focus of this research is on Foreign Workers (TKA) who wants to enter the territory of Indonesia. The data used is secondary data generated through the assessment of the literature related to this study.